2017
DOI: 10.1039/c7sm00345e
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative wrapping of nanoparticles of various sizes and shapes by lipid membranes

Abstract: Understanding the interaction between nanoparticles (NPs) and cell membranes is crucial for the design of NP-based drug delivery systems and for the assessment of the risks exerted by the NPs. Recent experimental and theoretical studies have shown that cell membranes can mediate attraction between NPs and form tubular structures to wrap multiple NPs. However, the cooperative wrapping process is still not well understood, and the shape effect of NPs is not considered. In this article, we use largescale coarse-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 65 publications
4
39
1
Order By: Relevance
“…However, the NPs are adsorbed by the membranes, pulled back, and finally embedded into the membranes. In SP-I, the membranes are not damaged in the stages, thereby exhibiting a good elasticity; the NPs are aggregated, as extensively reported in the previous simulations [15,23,53]. For the second mode, SP-II, as shown in FIG.…”
Section: A Translocation Modessupporting
confidence: 72%
See 1 more Smart Citation
“…However, the NPs are adsorbed by the membranes, pulled back, and finally embedded into the membranes. In SP-I, the membranes are not damaged in the stages, thereby exhibiting a good elasticity; the NPs are aggregated, as extensively reported in the previous simulations [15,23,53]. For the second mode, SP-II, as shown in FIG.…”
Section: A Translocation Modessupporting
confidence: 72%
“…Finally, the separation occurs, that is, the particles are separated from the membrane. Meanwhile, the NPs of various sizes can also be wrapped in different ways, in which the NPs are enclosed within the cell membranes [19,23,24]. The experimental and theoretical studies and the computer simulations have shown that the wrapped pathway is related to the sizes of NPs [14,25].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the area fraction and adhesion energy of the adsorbed Janus particle caps, we expect conformations in which several particles are cooperatively wrapped in tubular membrane segments, similar to the cooperative wrapping of uniformly adhesive spherical and non-spherical particles by membrane tubes. 15, [31][32][33][34][35] Our results identify the area fraction x of the adhesive Janus particle caps and the relative curvature c r of the particles and vesicles as experimentally accessible control parameters for the particle assembly. The relative curvature c r can be adjusted by varying the relative size of the Janus particles and the vesicle, and by confining the particles to the vesicle interior or exterior.…”
Section: Max Planck Institute Of Colloids and Interfaces • Authormentioning
confidence: 98%
“…[35] The large excess of membrane in colloidosome-loaded lysosomes accounts for the colloidosome flexibility, suggesting a reciprocal adaptation of host membranes to the colloidosome mechanical properties. [36] The coupling of membrane fluctuations to the colloidosome shell, giving rise to the so-called Helfrich entropic repulsion, [37,38] might favor colloidosome flattening and their concentration into the smaller, still more undulated, lysosomes observed at day 8. Lysosomes encapsulating dispersed NCs, which could be considered as the least perturbed system, show circularity of 0.75 at day 1 and it decreased to 0.59 at day 8.…”
Section: Lysosome Shapementioning
confidence: 99%